CONCEPT OF TOLERANCE IN THE SYSTEM OF SOCIAL ADAPTATION OF MIGRANTS AS A COMPONENT OF NON-FORMAL EDUCATION (ILLUSTRATED IN THE MODEL OF CANADIAN PROVINCE OF QUEBEC AND FRANCE) - Shtefan, Liudmyla; Rudnieva, Iryna; Kurnitska, Natalya; Lysenko, Natalya (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article deals with the notion of tolerance as one of the key values of modern democratic society, included in educational programs of universities, informal organizations, private foundations, religious communities promoting tolerance in the framework of non-formal education. The experience of Canada (classical approaches) and France (innovation) in the field of non-formal education is presented. Due to its flexibility, non-formal education plays a major role in the integration of migrants of different age, social and ethnic groups, determining the prospects for employment, social adaptation, personal development and participation in the state’s democratic life. The issue of socio-cultural adaptation of migrants is of great importance in the contemporary world due to such global undesirable processes as religious and ethnic conflicts, cases of racial discrimination. Migration is a natural process in the era of globalization, which, however, necessitates the adaptation of migrants to the host country’s cultural background. While European countries, recently experiencing an influx of migrants, are urgently searching for mechanisms for adapting the previous socio-cultural experience of migrants to the lifestyle, behavioral norms of the host country, Canadian province of Quebec has been efficiently using the tools of formal and non-formal education for over fifty years to build a more humane and tolerant attitude of citizens to each other, to eliminate conflicts and social aggression